Hospital managers’ experiences of conducting a root cause analysis: a case study following a sentinel event - Liepelt, Silje; Kirchhoff, Ralf (Frontiers in Health Services, 2025)
BackgroundRoot cause analysis (RCA) is a method used in healthcare to systematically identify and address underlying causes of adverse or sentinel events to enhance patient safety and mitigate risks. This study explores hospital managers' experiences of conducting an RCA process following a sentinel event in which a baby unexpectedly died during labor at a Norwegian hospital in 2021.MethodThe study employed a qualitative, exploratory single-case design, which involved conducting nine semi-structured interviews and analyzing documents such as the Norwegian RCA guideline, the final RCA report, and internal procedures and standards. The interviews were conducted between May and August 2021. Thematic analysis was used to organize and interpret the transcribed data. The research addressed the following question: What were the hospital managers’ experiences with conducting a root cause analysis?ResultsTwo main themes emerged. The first theme, challenges of and strategies for ensuring compliance with the Norwegian RCA Method, captures the wide range of challenges managers experience, ranging from practical application to communication breakdowns, role ambiguity, and meeting regulatory compliance. The second theme, emotional burden and support, underscores the emotional strain managers endured as they navigated the grief of the personnel involved, communicating with the bereaved family, and collaborated with external agencies during the investigation.ConclusionThe findings highlight the need for more precise role definitions, better resources, and stronger emotional support systems to strengthen RCA processes. Although national RCA guidelines provide a valuable framework, real-world constraints and unique circumstances often require adaptive approaches. This study emphasizes managers’ pivotal role in bridging the gap between regulatory expectations and organizational realities, underscoring the need for both practical and emotional support to ensure effective RCA implementation in sentinel events.